2012
DOI: 10.7243/2050-0866-1-24
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric type 2 diabetes mellitus complications: a systematic review of the literature

Abstract: The incidence and prevalence of type 2 diabetes mellitus (T2DM) are increasing worldwide in the pediatric population. The increase has been attributed to obesity, lack of physical activity, improper diet, and family medical history. Type 2 diabetes mellitus has serious complications for children, including cardiovascular problems, dyslipidemia, hypertension, nonalcoholic fatty liver disease, pancreatic problems, pulmonary problems, and renal injury. Unfortunately, T2DM and its complications in the pediatric po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The rate of increase in obesity prevalence in children and young adults might have stabilized during the recent decade [ 6 – 8 ]; however, 37% of older children are now overweight or obese in the United Kingdom [ 6 ]. Observational and genetic evidence from traditional cohort studies has suggested that obesity is a well-documented risk factor for type 2 diabetes [ 9 – 11 ]. However, recent evidence exploring the association of childhood obesity [defined as the 95th percentile for body mass index (BMI)] with the presence of pediatric diabetes in a real world primary care setting has been less well studied [ 12 14 ].…”
mentioning
confidence: 99%
“…The rate of increase in obesity prevalence in children and young adults might have stabilized during the recent decade [ 6 – 8 ]; however, 37% of older children are now overweight or obese in the United Kingdom [ 6 ]. Observational and genetic evidence from traditional cohort studies has suggested that obesity is a well-documented risk factor for type 2 diabetes [ 9 – 11 ]. However, recent evidence exploring the association of childhood obesity [defined as the 95th percentile for body mass index (BMI)] with the presence of pediatric diabetes in a real world primary care setting has been less well studied [ 12 14 ].…”
mentioning
confidence: 99%